A new discrete time delay control of hydraulic manipulators. (March 2017) - Wang, Yaoyao; Gu, Linyi; Chen, Bai; Wu, Hongtao
A new discrete time delay control design is presented and investigated for the joint-space control of hydraulic manipulators in this article. Thanks to the time delay estimation technique, our new designed controller no longer needs the detailed system model, which is very fascinating for practical applications. Also, the proposed discrete time delay control method requires no acceleration information to be obtained through quadratic differential, which is usually essential for the continuous-time version time delay control method of hydraulic manipulators. This may result in fewer requirements of computational effort or unavailability of sensors for obtaining the acceleration signal. Furthermore, the newly proposed discrete time delay control requires no future predicted values of the desired trajectory or system states compared with the traditional discrete time delay control method, which is more suitable for practical applications. The corresponding stability is analyzed using the bounded input bounded output stability theory. The easiness for actual applications and robustness against disturbance are verified through some 2-degree-of-freedom experiments.